Online privacy and security concerns of consumers. (10th October 2016) - Gurung, Anil; Raja, M.K.
Abstract : Purpose: Privacy and security concerns of consumers have been touted as one of the hindrances to the growth of e-commerce. These concerns increase the risk perception of consumers. Understanding the consequences of privacy and security concerns and their relationship to risk perceptions may provide a solution. The relationship between privacy and security is investigated using the theory of planned behavior. The study aims to examine the relationship of trust, privacy and security concerns to the risk perception adoption of e-commerce. The results from a survey validate the model. Design/methodology/approach: Data were collected using survey from undergraduate business students. The respondents were requested to select a specific product that they plan to purchase in the next six months. After selecting a product, the respondents were requested to report an online company that they have recently visited which offers the selected product. The respondents were requested to fill out the survey with regard to their selected online company. Time given was approximately 20 min. Findings: The results suggest that privacy and security concerns and trust beliefs had effects on risk perception. Among these effects, trust had the largest effect followed by privacy and security concerns. Furthermore, risk perception and trust beliefs had effects on attitude. The effect of trust beliefs on attitude was larger than the effect of risk perception on attitude. Similarly, subjective norm, perceived behavioral control and attitude had a positive and direct effect on intention to be involved in e-commerce. Research limitations/implications: The first limitation of this study is the use of student subjects. Because this study took place in an educational setting, its generalizability to the general population of consumers lacks to some degree. The second limitation of this study is mono-method bias. Practical implications: The effect of privacy concerns on risk perception was larger than that of security concerns. Because the consumers get more experienced and sophisticated using the Web, the security concerns that they may have had at the beginning are not reflected in their risk perceptions. It is likely that they have adopted protective measures on their own to defend their privacy online. An example of such a measure would be providing false information to online companies when asked to submit personal information. Originality/value: The major contributions of this study are developing and validating an integrative framework of e-commerce adoption at the individual level. The model includes privacy and security concerns, risk perception and trust beliefs. This study also highlighted the distinction of constructs of privacy and security concerns and showed their differential effects on other related constructs in the research model.